Juridical Implications of Unregistered Marriage Against Legal Protection in the Domestic Violence Law - Peter Jeremiah Setiawan; Xavier Nugraha; Desak Ayu Gangga Sitha Dewi; Marchethy Riwani Diaz (Media Iuris, 2023)
This article aims to analyze the juridical implications of not registering marriages for legal protection for the community, because the existence of the PKDRT Law has not been fully able to guarantee legal protection. The writing method used is juridical-normative using a reform-oriented research typology, namely evaluating applicable rules by providing recommendations on these rules. This study concludes that there is a blurring of legal subjects that can be protected in the PKDRT Law due to differences of opinion regarding the validity of marriage based on the provisions in Article 2 of the Marriage Law. Moreover, there are differences in judges’ views on the validity of a marriage which are not recorded in several decisions of cases of domestic violence causing legal uncertainty. However, there is still an alternative for self-protection for victims of domestic violence whose marriages have not been registered, namely using the articles in the Criminal Code.